Current status and influencing factors of health literacy among older adults in combined medical and nursing care institutions: a cross-sectional study - Tao, Simin; Sun, Silu; Wu, Shiying; Peng, Tao; Cao, Li; Yan, Min; Ma, Jie; Li, Hui (Frontiers in Public Health, 2024)
Health literacy is linked to the health status of older adults and is a critical component in achieving active aging. To this end, we conducted a cross-sectional study to characterize the current health literacy status among older adults in combined medical and nursing care institutions, as well as the factors that influenced this status. We used a convenience sampling method to select 740 older adults who were in 16 combined medical and nursing care institutions in Chengdu, China, from July 2022 to June 2023, using the Health Literacy Management Scale, the Social Support Rating Scale, and the Short Form-36 Health Survey. The results showed a health literacy score of 75.25 ± 12.33, a social support score of 37.37 ± 6.10, and a health-related quality of life score of 55.34 ± 15.48. Factors influencing health literacy included age, educational level, previous occupation, family size, monthly per capita household income, and healthrelated quality of life. Health literacy is an essential factor in improving the health status of older adults. We should therefore improve health education and health promotion interventions for older adults in combined medical and nursing care institutions to improve health literacy.